Integration in Rome and in the Roman World Proceedings of the Tenth Workshop of the International Network Impact of Empire (Lille, June 23-25, 2011) - de Kleijn, Gerda; Benoist, Stéphane (Impact of Empire, 2013)
Integration in the empire under the political control of the city of Rome, her princeps, and the different authorities in the provinces includes processes of inclusion and exclusion. They are explored from juridical, political, social and religious points of view. Readership: Scholars and students interested in Roman history, from the Republic to the Late Antiquity; historians, classicists, philologists, as well as philosophers and specialists on Social history, History of Religions and Cultural Studies.